The Impact of Online Game Application Addiction and Its Implications on Communication Patterns and Self-Management in Children at SMP Muhammadiyah 57 Medan - Irfan, Muhammad; Nashrillah (Journal of Communication Studies, 2025)
This article aims to present data on the impact of online game addiction and its implications for communication and self-management among students at SMP Muhammadiyah 57 Medan. Online games are internet-based games that can be widely accessed by anyone, anywhere. Their presence is now familiar to both children and adults. Along with technological advancements, online games continue to introduce new and engaging features that attract many users. However, excessive use can lead to addiction, which has negative implications for users. This study employs a qualitative descriptive approach, with data collected through interviews and documentation. The research subjects include five students and one guidance and counseling teacher at SMP Muhammadiyah 57 Medan. The results indicate that online game addiction affects several aspects of students’ lives. The impacts include physical health issues due to lack of activity, decreased learning motivation and academic achievement, changes in social interactions, psychological disturbances such as emotional instability, and even financial problems caused by spending money on gaming. Thus, online game addiction is not merely a matter of entertainment, but is closely related to students’ self-management—particularly in regulating their time, emotions, and academic responsibilities.